Kelainan refraksi pada siswa SMP daerah pedesaan - Mamesah, Indo; Saerang, Josefien S. M.; Rares, Laya M. (e-CliniC, 2016)
Abstract: Visual impairment is defined as a functional limitation of the eye/eyes or visual system and can manifest in decreased visual acuity or contrast sensitivity, visual field loss, photophobia, visual distortion, visual perceptual difficulties, or a combination of them. Examination of the eye and vision assessment are very important to detect conditions that can cause blindness and serious systemic conditions, which cause problems in school performance, or at a more severe level, life threatening. This study aimed to obtain the occurence of refractive anomalies among junior high school students in rural areas. This was an analytical observational study with a cross-sectional design. The study was conducted in SMP I Wori (rural area) and SMP I Airmadidi (urban area). There were 60 respondents; 30 respondents of each school. Distributions of respondent genders were nearly the same for both schools; the number of females was higher than males. The majority of SMP I Airmadidi students were 11 years old (36.7%), meanwhile the majority of SMP Wori students were 13 years (50%). Most student complaints in SMP I Airmadidi were itchy eyes and drowsiness (16.7%), meanwhile in SMP I Wori was headache (18.4%). Visual impairment was found in 16.6% of students of SMP I Airmadidi, meanwhile in SMP I there was no student with refractive anomaly. Conclusion: There was no refractive anomaly found among students of rural area, however, among students of urban area myopia was the refractive anomaly found.Keywords: refractive anomalyAbstrak: Gangguan penglihatan didefinisikan sebagai suatu keterbatasan fungsional pada mata atau kedua mata atau sistem visual yang dapat bermanifestasi terhadap penurunan ketajaman penglihatan atau sensitifitas kontras, hilangnya lapangan penglihatan, photofobia, distorsi visual, kesulitan perseptual visual atau kombinasi dari semua diatas. Pemeriksaan mata dan penilaian penglihatan sangat penting untuk mendeteksi kondisi yang dapat menyebabkan kebutaan dan kondisi sistemik serius, yang memicu masalah performa di sekolah, atau pada tingkat yang lebih berat, mengancam kehidupan anak. Penelitian ini bertujuan untuk mengetahui gambaran kelainan refraksi pada anak SMP di daerah pedesaan. Jenis penelitian ini analitik observasional dengan desain potong lintang. Penelitian dilakukan di SMPN I Wori (daerah luar Minahasa Utara/pedesaan) dan SMPN I Airmadidi (kota Kabupaten Minahasa Utara), dan diperoleh 60 responden penelitian. Distribusi jenis kelamin responden kedua sekolah hampir sama dimana jumlah perempuan lebih banyak dari laki-laki. Usia terbanyak di SMPN I Airmadidi ialah 11 tahun (36,7%) sedangkan di SMPN Wori 13 tahun (50%). Keluhan terbanyak siswa di SMPN I Airmadidi ialah mata gatal dan rasa kantuk (16,7%), sedangkan di SMPN I Wori ialah sakit kepala (18, 4%). Gangguan penglihatan ditemukan pada responden di SMPN I Airmadidi sebanyak 16,6 % sedangkan di SMPN I tidak ditemukan kelainan visus. Simpulan: Tidak ditemukan adanya gangguan refraksi pada siswa SMP di daerah pedesaan. Kelainan refraksi miopia ditemukan pada siswa SMP di perkotaan.Kata kunci: gangguan refraksi